The Cuitzeo granitic xenolith: evidence of an Early Miocene magma plumbing system in central Mexico - María del Sol Hernández-Bernal; Pedro Corona-Chávez; Noemí Trujillo-Hernández; Consuelo Macías-Romo; Dante Jaime Morán-Zenteno; Adrián Jiménez-Haro; Stefano Poli (Revista Mexicana de Ciencias Geológicas)
Relevant data on the structure and composition of the crystalline basement in Central México can be found by means of plutonic, metamorphic, and sedimentary xenoliths transported by Neogene and Quaternary volcanic eruptions within the Trans-Mexican Volcanic Belt (TMVB). We present detailed major oxide and trace elements concentrations, isotopic analysis and thermobarometric estimations for a granitic xenolith found in an Early Miocene ignimbrite in Cuitzeo Lake, Michoacán. The xenolith is a calc-alkaline quartz-plagioclase-K-feldspar-biotite-amphibole granite-monzogranite with 73.7 wt.% SiO2. Trace element and isotopic signatures are compatible with a volcanic arc signature. According to amphibole-plagioclase pairs and Ti-in-zircon thermobarometry, the studied xenolith suggests that the granitic system crystallized between 655–737 °C and 1.3–1.9 kbar. U-Pb isotopic analyses of zircon grains from this rock have provided a concordia age of 20.76 ± 0.11 Ma. The presence of granitic xenoliths in Quaternary eruptions produced by the TMVB are not rare. However, this is the first zircon age of a Miocene granitic rock showing evidence of the shallow plutonic counterpart of the magma plumbing system of the Early Miocene (~23 to ~16 Ma) Mil Cumbres - Angangueo voluminous, andesitic-dacitic-rhyolitic episode. Implications for faulting, erosion, and Miocene-Pliocene ignimbrite emplacement in Cuitzeo region are also discussed.